PENGGUNAAN DOSIS HORMON OVAPRIM YANG BERBEDA TERHADAP OVULASI INDUK BETINA IKAN SERUKAN, Osteochilus sp. (Cyprinidae) - Afrizal Hendri (Universitas Teuku Umar, 2015)
This research aims to knowing latency and fish ovulation of Osteochilus sp. after injected with different doses. The research was counducted on January – March 2015. For experimental design, this study have been using completely randomized design, consist of 3 treatment, 1 control and 3 replication. The result of this study show significant effect to latency and ovalation of fish (Osteochilus sp) (F > 0.05). The better treatment is found in P3 (0,5 mL/kg), with average value of ovalation is 100% and average value of latency is 33 hours.